The role of mucosal barriers in human gut health - Seo, Kangseok; Seo, Jeongmi; Yeun, Jiyoun; Choi, Haebin; Kim, Young In; Chang, Sun Young (Archives of Pharmacal Research, 2021)
The intestinal mucosa is continuously exposed to a large number of commensal or pathogenic microbiota and foreign food antigens. The intestinal epithelium forms a dynamic physicochemical barrier to maintain immune homeostasis. To efficiently absorb nutrients from food, the epithelium in the small intestine has thin, permeable layers spread over a vast surface area. Epithelial cells are renewed from the crypt toward the villi, accompanying epithelial cell death and shedding, to control bacterial colonization. Tight junction and adherens junction proteins provide epithelial cell–cell integrity. Microbial signals are recognized by epithelial cells via toll-like receptors. Environmental signals from short-chain fatty acids derived from commensal microbiota metabolites, aryl hydrocarbon receptors, and hypoxia-induced factors fortify gut barrier function. Here we summarize recent findings regarding various environmental factors for gut barrier function. Further, we discuss the role of gut barriers in the pathogenesis of human intestinal disease and the challenges of therapeutic strategies targeting gut barrier restoration.
Keywords: Epithelial Cells; Gastrointestinal Microbiome; Humans; Intestinal Mucosa; Barrier function; Epithelial cell; Gut; Inflammation; Inflammatory bowel disease